Hubungan Persepsi dan Motivasi dengan Pemberantasan Sarang Nyamuk 3M PLUS sebagai Upaya Pencegahan Demam Berdarah Dengue - Ratna Dian Kurniawati; Irna Rohmawaty; Agung Sutriyawan (Jurnal Kesehatan Indonesia, 2022)
Case fatality rate of Dengue Hemorrhagic Fever (DHF) in the work area of the Cinunuk Community Health Center is quite high at 40 cases (3%). One of the problems that make DHF recurring is the people's trust in the effectiveness of fogging. People are familiar with Mosquito Nest Eradication (PSN) 3MPlus. However, people are more likely to do the DBD vector control by fogging. PSN 3MPlus is a program that is expected to cope with DHF. PSN 3MPlus is believed to be more effective in breaking the life cycle of the Aedes sp. The purpose of this study was to determine public perception and motivation by implementing the PSN 3MPlus as a preventive measure for dengue in the work area of the Cinunuk Health Center in 2019. The research design used a cross-sectional. Sampling with Multi-Stage Random Sampling was 76 households. The measuring instrument used was a questionnaire. The results showed that 71.1% of family heads did not implement the PSN 3MPlus, 65.8% of family heads had poor perceptions, and 60.5% of family heads had poor motivation. Based on the research there is a correlation between perception (p-value 0,000 ? 0,001 and POR CI 95% 6,125), motivation (p-value 0,000 ? 0,000 and POR CI 95% 10,723) with the implementation of PSN 3MPlus. There was a significant correlation between perception and motivation with the implementation of the PSN 3Mplus.